Computed tomographic appearance of laryngeal lesions in 7 dogs - Slusarek, Anna; Hamaide, Annick; Lefebvre, Michaël; Heimann, Marianne; Billen, Frédéric; Bolen, Géraldine (Frontiers in Veterinary Science, 2025)
ObjectiveTo describe the computed tomographic (CT) features of neoplastic and inflammatory laryngeal masses. The authors hypothesized that specific CT features may help differentiate between these two origins and that regional lymph nodes would be larger in cases of laryngeal neoplasia.MethodsMedical records from two veterinary referral hospitals were screened for dogs diagnosed with either an inflammatory or neoplastic laryngeal mass who underwent CT scans of the neck. Information retrieved from medical records included signalment, physical examination findings, CT scan findings, and definitive diagnosis of the laryngeal mass based on cytological or histopathological results.ResultsFour dogs had laboratory reports compatible with a malignant neoplasia and three with an inflammatory process. The shape of the mass was defined as “ovoid” in all neoplastic masses and as “thickening” in cases of inflammatory processes. Masses were of various sizes (median length: 42 mm, range: 26–82 mm) and either unilateral (1/4 and 2/3 of neoplastic and inflammatory masses respectively) or bilateral. They were described as mineralized (1/4 and 1/3) and as having either an internal (1/4), external (2/4) growth pattern or both (1/4, 3/3). All masses had ill-defined margins and showed heterogeneous contrast enhancement. Two neoplastic and two inflammatory masses had a cavitary aspect. All but one case were associated with regional lymphadenopathy. Thyroid cartilage destruction was observed with two neoplastic and two inflammatory masses.Clinical relevanceThis case series describes CT features of laryngeal masses. The shape of the laryngeal mass may assist in determining its nature, inflammatory process was defined as “thickening” of the larynx and neoplasia as “ovoid”-shaped, whereas other studied features were inconsistently observed in both neoplastic and inflammatory conditions.